PENGARUH KEMAMPUAN MEMBACA ALQUR’AN TERHADAP HASIL BELAJAR MAHASISWA POLITEKNIK NEGERI MEDAN - Suherman Suherman (Universitas Islam Negeri Sumatera Utara Medan, 2017)
ABSTRACT This article is the result of research to find information about student's ability and persistence to read Alqur'an and its effect on result of learning. The research method used is f test and t test and analyzed with simple linear regression statistic formula. This research was conducted on 46 students of Energy Conversion Technique State Polytechnic of Medan.Data collection techniques are observation, interview, questionnaire and oral and written test. Based on the statistical analysis concluded that the data show the hypothesis of researchers have been tested empirically that the ability to read Alqur'an has an influence on student learning outcomes. This is indicated by Fcount> F table (106.726> 4.06), so Ho is rejected and Ha accepted. Also indicated by the test tcount> ttable = (10.331> 2.01537).This means that there is a linear, positive and significant influence between the ability to read Alqur'an on student learning outcomes. Improved student learning outcomes are influenced by the ability to read Alqur'an 70.1%. The rest of the students' learning outcomes are influenced by factors that are not observed in this study that is equal to 29.9%.This finding becomes a great opportunity for the effort to improve student's learning achievement by way of guiding the ability of reading the official and sustainable Alqur'an. Concrete students need to be motivated to form groups (halaqah) Alqur'an on campus whose activities can be up to Polmed even by using media on line. For lecturers also have to give rewards for students who are diligent and have good reading ability, let alone he has a good recitations talent and has achievements in MTQN. Keywords: ability to read Alqur'an, learning outcomes, improvement of achievement